Open Access scholarly literature on Gastritis (2002-2021) in Web of Science: A Scientometric Analysis - Amanullah, Amir; S Rajeswari (International journal of economic perspectives, 2022)
The present study is an endeavor to quantify the publication productivity on worldwide gastritis research output (open access) with the help of the available scientometric indicators and tools. The study discovered that there is an improvement in the Priority Index/Activity Index value of India from 2010. The RGR and DT values are calculated as 0.18 and 4.81 respectively while as the Degree of Collaboration is 0.967. Yamaoka Y, Malfertheiner P and Graham DY are the top three contributing authors, World Journal of Gastroenterology, Plos One and Alimentary Pharmacology & Therapeutics are the top three journals that contributed most open access publications on gastritis. The top 20 most productive journals form the core zone journals which contribute to 33.26% of the total publications. USA, China and Japan occupy the top three positions in the list of prolific nations while as India ranks 16th. 35% of the total publications received citations in the range of 1-10 while as 3 publications received more than 1000 citations each.